Brunner Glands. Issue 4 (July 2015) - Lastra, Ricardo R.; Jhala, Darshana N.; Ahmad, Nuzhat A.; Jhala, Nirag C.
<x xml:space="preserve">Abstract</x> Abstract The development of the flexible fiberoptic endoscope and the ability to obtain endoscopic ultrasound–guided fine-needle aspirations of the pancreas has significantly changed the management of patients with pancreatic lesions. Cytopathologists have understood the diagnostic criteria applied to these relatively new specimens and have learned to recognize normal gastrointestinal contaminants that might be encountered in the smears. Well-recognized examples of such contaminants include duodenal and gastric epithelium. To date, however, no one has reported the presence of Brunner gland epithelium as a contaminant in these specimens. We report 2 cases in which normal Brunner gland epithelium was interpreted as lesional tissue in cytology preparations, leading to surgical procedures. By describing the cytomorphologic features of these cells, we hope to create awareness of this finding as a potential pitfall in these samples.